Propeller Sledges on the German Greenland Expedition, 1930–31 - Schif, Curt (Polar Record, 1936)
Modern polar research calls for a much more specialised and efficient travel technique than did polar exploration of even a few years ago; and, as a result, great strides have been made in perfecting the modern mechanical methods of transport. The old method of dog-sledging, with its comparatively low speeds and light loads, is already being replaced, to some extent, by mechanically driven sledges and aeroplanes. Several expeditions at work in the Arctic and Antarctic during the last few years have been able to make excellent use of air transport, but the first mechanically driven sledges were at best only moderately successful, and each reached its limit according to its construction either as a result of bad ice, slush, or deep powder snow, where the wheels or caterpillar band became bogged.